(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Chiari type I malformation is a neurological condition defined by downward displacement of the cerebellar tonsils through the foramen magnum into the spinal canal. It is frequently accompanied by syringomyelia, hydrocephalus, and myelomeningocele. With the advent of advanced neuroimaging, earlier recognition has become possible, prompting timely surgical intervention. The most widely practiced procedures include posterior fossa decompression, with or without duraplasty, and cerebrospinal fluid diversion techniques. This review critically examines the range of surgical strategies, outlining their benefits, limitations, and reported outcomes. Current evidence supports surgery only for symptomatic patients, with earlier intervention often linked to better recovery. Despite numerous clinical reports, the absence of large-scale, standardized trials continues to hinder the development of universally accepted surgical guidelines. This abstract also underscores the historical evolution of Chiari malformation classification, the controversies surrounding duraplasty, and the importance of individualized treatment planning. By integrating epidemiological data, surgical outcomes, and future research directions, this review aims to provide a comprehensive synthesis for clinicians and researchers alike.